Eclectic Visual Narrative: Nine Paintings About Indonesian Culture of Nautical Society - Nalan, Arthur S.; Sustiawati, Ni Luh; Jatnika, Anggit (UPT Pusat Penerbitan LP2MPP ISI Bali, 2023)
This research discusses an eclectic visual narrative of nine paintings about the Indonesian nautical culture by Arthur S. Nalan. Nautical society inhabits all the coasts of the Indonesian archipelago and relies on maritime-related livelihoods. Nautical society is rarely used as a source for artistic creation. This research uses the Practice-Based Research method edited by Craig Vear (2022), applying the theory of the Aesthetic Communication approach of Ole Thyssen (2010), which describes identity, vision, and image: initial remarks. Therefore, the nine paintings studied in this research can be understood as a pneumonic device for those who recognize, understand, and appreciate the Indonesian nautical culture. The research was carried out through the process of “analyzing” nine paintings by Arthur S. Nalan. The finding in this research is an eclectic visual narrative of the Indonesian nautical culture. This research concludes that the nine paintings present the dynamics of the Indonesian nautical culture.